Herbal Dentistry: Nurturing Oral Health with Natural Remedies - Surabhi Duggal; P. Sindhu Chandrika; Fazil A. Nasyam; Dhirendra K. Singh; Indira M. Devraj; Charu Anand (Wolters Kluwer Medknow Publications, 2024)
Herbal dentistry, also known as natural or holistic dentistry, is a field of dental care that utilizes natural remedies and herbal medicine to prevent and treat oral health issues. This approach focuses on the use of herbs, plant extracts, and other natural substances to promote oral hygiene and address dental problems. In recent years, there has been a growing interest in herbal dentistry as an alternative to conventional dental treatments. This comprehensive review aims to explore the use of herbal remedies in dentistry, their potential benefits, and their limitations.